Effects of provided trainings regarding non-invasive mechanical ventilation on the knowledge level of nurses - Göktaş, Sonay; Kıraner, Ebru; Doğan, Pınar; Tunalı, Berrin (My University, 2017)
Objective: Having experienced members in the team for obtaining successful outcomes in non-invasive mechanical ventilation (NIMV) is important. The aim of our study is to determine the effectiveness of training on nurse's level of knowledge about NIMVMethods: This study was done with 70 nurses who were working at an university hospital. The data collection tools that were used were form for individual characteristics and knowledge test questions form consisting of multiple-choice for NIMV. Firstly, Pre-tests have been collected in the survey. Secondly, courses regarding NIMV indications, contraindications and patients management topics were given verbally by researchers. Finally, final tests were performed and data were collected. Analyzing for data were used frequency, percentage, wilcoxon and dependent samples Mc Nemar tests. Results: Mean age were 33.2±7.3, 87.1% were female, 68.6% had bachelor degrees. Of 47.1% were working in intensive care. 54.3% often provide care to NIMV applied patients. 94.7% mentioned that they don't have any knowledge of NIMV applications. The differences between the pre-post training scores were higher statistically (p<0.001). It was determined that knowledge levels of nurses about NIMV indications and contraindications after training increased statistically significantly. (p<0.05). Conclusion: In our research it was understood that nurses' knowledge has increased significantly after the training for non-invasive applications. By means of these trainings that will develop the affective, cognitive and psychomotor skills of nurses, it is expected to reveal the results of the extensive research and successful outcomes for NIMV applications will increase.
Keywords: Level of Knowledge; Noninvasive Mechanic Ventilation; Nurse